2023
DOI: 10.3390/biomedicines11102732
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Injury-Related Predisposing Factors of Post-Traumatic Stress Disorder: A Critical Examination

Wiley Gillam,
Nikhil Godbole,
Shourya Sangam
et al.

Abstract: The present review aimed to identify the means through which neurologic injury can predispose individuals to Post-Traumatic Stress Disorder (PTSD). In recent years, comprehensive studies have helped to clarify which structures in the central nervous system can lead to distinct PTSD symptoms—namely, dissociative reactions or flashbacks—when damaged. Our review narrowed its focus to three common neurologic injuries, traumatic brain injury (TBI), subarachnoid hemorrhage (SAH), and stroke. We found that in each of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…The link between injuries, concussions, and CTE has become a major area of research in recent years, particularly in the context of professional sports. Furthermore, numerous studies indicated a correlation between traumatic brain injury (TBI) and post-traumatic stress disorder (PTSD), and demonstrated role of TBI in rendering individuals more susceptible to developing PTSD ( 32 , 33 ). Moreover, we also found that the pathology of CTE captured the attention of the general public and scientific community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between injuries, concussions, and CTE has become a major area of research in recent years, particularly in the context of professional sports. Furthermore, numerous studies indicated a correlation between traumatic brain injury (TBI) and post-traumatic stress disorder (PTSD), and demonstrated role of TBI in rendering individuals more susceptible to developing PTSD ( 32 , 33 ). Moreover, we also found that the pathology of CTE captured the attention of the general public and scientific community.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of abnormal tau protein in the brain into neurofibrillary tangles is one of hallmarks of CTE ( 34 ). In addition to CTE, abnormal aggregation of tau protein also occurs in other neurodegenerative diseases like AD and dementia ( 32 , 35 ). They may differ in the location, morphology, and severity of aggregation ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mind-body techniques have been shown to reduce the adverse effects of stress and trauma on child and adult survivors of war and other mass disasters [49][50][51][52] 1). Although in-person BBM studies have used standardized measures of anxiety, depression, and PTSD [13], online studies did not use PTSD test measures [55,56]. In trials, such as for RISE, as a government agency, the evaluators specifically avoided using tests that could be used to diagnose any psychological disorder in the employees.…”
Section: Effects Of Breath-centered Mind-body Practices In Children A...mentioning
confidence: 99%